2021
DOI: 10.1371/journal.pgen.1009094
|View full text |Cite
|
Sign up to set email alerts
|

Transposon mutagenesis identifies cooperating genetic drivers during keratinocyte transformation and cutaneous squamous cell carcinoma progression

Abstract: The systematic identification of genetic events driving cellular transformation and tumor progression in the absence of a highly recurrent oncogenic driver mutation is a challenge in cutaneous oncology. In cutaneous squamous cell carcinoma (cuSCC), the high UV-induced mutational burden poses a hurdle to achieve a complete molecular landscape of this disease. Here, we utilized the Sleeping Beauty transposon mutagenesis system to statistically define drivers of keratinocyte transformation and cuSCC progression i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…To assess the generalizability of our models, we repeated this analysis in multiple previously described datasets ( 23 , 25 , 37 , 46 ) as well as the tail samples generated in our DLBCL experiments, which serve as negative, unselected controls. Overall, we found the predictive power of the various individual features to be similar between datasets ( Supplementary Figure S2A and B ), with some noticeable exceptions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the generalizability of our models, we repeated this analysis in multiple previously described datasets ( 23 , 25 , 37 , 46 ) as well as the tail samples generated in our DLBCL experiments, which serve as negative, unselected controls. Overall, we found the predictive power of the various individual features to be similar between datasets ( Supplementary Figure S2A and B ), with some noticeable exceptions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to our newly generated DLBCL dataset, we analysed other datasets described in previous publications. Specifically, we examined screens from cohorts developing acute myeloid leukaemia (AML), cutaneous squamous cell carcinoma (cuSCC), hepatocellular carcinoma (HCC), and gastrointestinal tumours (Intestinal) ( 23 , 25 , 46 ), as well as insertions in mouse embryonic stem cells (mESC) ( 37 ). If insertion sites in these datasets had been mapped to the mm9 version of the mouse genome, a lift-over to mm10 was performed using the UCSC chain file.…”
Section: Methodsmentioning
confidence: 99%
“…Using whole-genome sequencing, Thind et al demonstrated significant recurrent copy number loss in the tumor suppressor genes KANSL1 and PTPRD [ 16 ]. Likewise, KMT2C , CREBBP , and NCOA2 were identified to demonstrate tumor-suppressive roles in the initiation and progression of human cSCC [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aiderus et al defined two mutually exclusive paralogous oncogenic drivers, Zmiz1 and Zmiz2 , among the most recurrent drivers of cSCC development. Interestingly, all cSCC tumors with Zmiz1/2 insertions had inactivating insertions in at least one gene involved in chromatin remodeling, suggesting that alterations in epigenetic regulation are essential in cSCC development [ 17 ]. Actin-like protein 6A ( ACTL6A , BAF53a ) is a key protein subunit of the SWI/SNF epigenetic chromatin regulatory complex.…”
Section: Resultsmentioning
confidence: 99%
“…Equally, the role of ZMIZ2 as a fusion partner remains poorly understood, however, some data is suggesting its importance as an oncogenic driver in cutaneous squamous cell carcinoma. 39 ZMIZ2 is a member of the protein inhibitor of the activated STAT-like family and interacts with nuclear hormone receptors such as AR (Huang et al…”
Section: Immunohistochemical Findingsmentioning
confidence: 99%